Optimizing the Role of Teachers and Students in the Digital Era in Facing VUCA Challenges - Jufriansah, Adi; Ma'rup; Khusnani, Azmi (Journal of Social and Community Development, 2024)
In the rapidly developing digital era, technologies such as Artificial Intelligence (AI), Blockchain, Internet of Things (IoT), Augmented Reality (AR), Virtual Reality (VR), and Artificial Intelligence of Things (IoT) are becoming an integral part of education. The role of teachers and students needs to be adapted to utilize this technology effectively in facing the challenges of VUCA (Volatility, Uncertainty, Complexity, Ambiguity). This community service aims to identify strategies that can be implemented by teachers and students to utilize digital technology, as well as explore its impact and benefits in education. In addition, this community service will also examine how this technology can help reduce uncertainty and complexity in a changing educational environment. The evaluation results showed excellent achievements with high scores for conceptual understanding and overall benefits, confirming that this activity provides a solid foundation for developing education responsive to the demands of the times, especially in the current VUCA era.